2017
DOI: 10.1186/s13071-017-2300-8
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic insight into the midgut proteome of Ornithodoros moubata females reveals novel information on blood digestion in argasid ticks

Abstract: BackgroundThe argasid tick Ornithodoros moubata is the main African vector of the human relapsing fever agent Borrelia duttoni and the African swine fever virus. Together with saliva, the tick midgut forms part of the host-tick-pathogen interface, and numerous midgut proteins play key functions in the blood digestion-related process and the infection and transmission of pathogens. This work explores the composition of the midgut proteome of unfed and fed O. moubata females with the aim to complete the biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 72 publications
(85 reference statements)
1
22
0
Order By: Relevance
“…In Schyzosaccharomyces pombe, calnexin overexpression is involved in the induction of apoptosis triggered by endoplasmic reticulum stress (Guérin et al, 2008). In the midgut of the argasid tick Ornithodoros moubata female, a calnexin protein has been identified and determined to be involved with the stress responses associated with blood digestion (Oleaga et al, 2017). A calnexin transcript was upregulated in the Ixodes ricinus-derived cell line IRE/CTVM19 at day 2 post-infection with the flavivirus tickborne encephalitis virus (TBEV), which may have an important role in the response of tick cells to virus infection (Weisheit et al, 2015).…”
Section: Degs Between Ticks Fed On Tick-susceptible and Resistant Cattlementioning
confidence: 99%
See 2 more Smart Citations
“…In Schyzosaccharomyces pombe, calnexin overexpression is involved in the induction of apoptosis triggered by endoplasmic reticulum stress (Guérin et al, 2008). In the midgut of the argasid tick Ornithodoros moubata female, a calnexin protein has been identified and determined to be involved with the stress responses associated with blood digestion (Oleaga et al, 2017). A calnexin transcript was upregulated in the Ixodes ricinus-derived cell line IRE/CTVM19 at day 2 post-infection with the flavivirus tickborne encephalitis virus (TBEV), which may have an important role in the response of tick cells to virus infection (Weisheit et al, 2015).…”
Section: Degs Between Ticks Fed On Tick-susceptible and Resistant Cattlementioning
confidence: 99%
“…Four phosphate-adaptor proteins 1 and 2 (FAPP1 and FAPP2) are proteins that localize to the trans-Golgi network (TGN) on nascent carriers and interact with phosphatidylinositol-4-phosphate and the small GTPase ADPribosylation factor (ARF) through their plekstrin homology domain (Godi et al, 2004). Phosphoinositol 4-phosphate adaptor proteins are involved in lipid transport (Oleaga et al, 2017) and control the formation and fission of post-Golgi vesicles and regulate secretory transport from the TGN to the plasma membrane, and displacement or knockdown of FAPPs inhibits cargo transfer to the plasma membrane (Godi et al, 2004). In Ornithodoros moubata ticks, phosphoinositol 4-phosphate adaptor protein transcripts were upregulated in the midgut after blood feeding in comparison with non-fed ticks (Oleaga et al, 2017).…”
Section: Degs Predicted As Salivary Gland Secreted Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Choice of 'shot-gun' technology will be important. Use of liquid chromatography and tandem mass spectrometry analysis (LC/MS-MS) of the mid-gut proteome of O. moubata females failed to find great differences in the number or class of proteins expressed, enzymatic composition or functional classification before and after blood feeding- Oleaga et al (2017). This was despite a detailed analysis of particular groups of proteins that are involved in the processes of nutrient digestion and responses to the oxidative stress being carried out.…”
Section: Looking To the Futurementioning
confidence: 99%
“…ROS and RNS appear to be substantial environmental challenges for B. burgdorferi during both blood meal acquisition and during starvation in I. scapularis nymphs, as ROS‐sensitive and RNS‐sensitive B. burgdorferi strains harbouring mutations in antioxidant defence genes show poor survival compared with their wild‐type counterparts (Bourret et al, ; Eggers et al, ; Li et al, ). To the best of our knowledge, the production of ROS and RNS in Ornithodoros ticks has not been reported; however, transcriptomic and proteomic studies have identified a variety of oxidant metabolism and antioxidant defence genes expressed in soft‐bodied ticks that transmit RF Borrelia (Francischetti, Mans, et al, ; Francischetti, Meng, et al, ; Landulfo et al, ; Oleaga, Obolo‐Mvoulouga, Manzano‐Roman, & Perez‐Sanchez, ; Oleaga, Obolo‐Mvoulouga, Manzano‐Roman, & Perez‐Sanchez, ; Oleaga, Obolo‐Mvoulouga, Manzano‐Roman, & Perez‐Sanchez, ).…”
Section: Introductionmentioning
confidence: 99%